(untitled) (Al-Mansour Journal, 2025)
The semantic significance of Qur’anic context is considered one of the most important interpretive tools employed by exegetes in elucidating the meanings of the Holy Qur’an and deriving its rulings. This study, therefore, gains its importance from its focus on examining the contextual significance and its impact on the extraction of Qur’anic meanings. The meaning of a Qur’anic verse or phrase cannot be accurately understood without considering the preceding and following context in which it appears. The meaning conveyed through context holds various dimensions and offers numerous benefits, as pointed out by prominent scholars and exegetes of both early and later generations.